2012
DOI: 10.1097/meg.0b013e328356ae49
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam for sedation during diagnostic or therapeutic upper gastrointestinal endoscopy in cirrhotic patients

Abstract: We concluded that intravenous midazolam can be used safely in cirrhotic patients of Child-Pugh class A and B undergoing UGE for conscious sedation, but caution should be exercised for patients with advanced liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
3
20
1
Order By: Relevance
“…Interestingly, overt HEP after EVL under sedation developed only in 0.4% of patients, which is a lower incidence than that reported in a previous study [12] . We believe that this outcome may be due to the use of flumazenil to reverse the sedative effect of midazolam.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Interestingly, overt HEP after EVL under sedation developed only in 0.4% of patients, which is a lower incidence than that reported in a previous study [12] . We believe that this outcome may be due to the use of flumazenil to reverse the sedative effect of midazolam.…”
Section: Discussioncontrasting
confidence: 48%
“…However, it is a short-acting benzodiazepine, and flumazenil is a rapidly-acting midazolam antidote [4][5][6][7] . In a previous study, it was reported that intravenous midazolam can be considered safe in patients with compensated LC [12] . However, this previous study was limited by the use of retrospective data; 4.2% of the enrolled patients had previous experience of overt HEP, and patients administered flumazenil were excluded.…”
Section: Introductionmentioning
confidence: 99%
“…24 Dexmedetomidine and midazolam were used in the present study because these drugs have distinctive pharmacological profiles and their respective adverse effects require different management strategies. 10,18,19 Dexmedetomidine is commonly administered as a bolus of 0.5-1.0 mg/kg, followed by an infusion of 0.2-2.0 mg/kg per h. The initial loading dose may cause adverse cardiovascular reactions such as hypertension, hypotension, bradycardia or sinus arrest, especially in patients taking medication capable of producing negative chronotropic effects (e.g. b-adrenergic antagonists and digoxin) or those with hypovolaemia.…”
Section: Discussionmentioning
confidence: 99%
“…10 Midazolam was selected as the medication for comparison in our study owing to its frequent use as a sedative in gastroscopy and endoscopy. 10,18,19 Midazolam is usually used alone for gastroscopy and is combined with opioids (meperidine or fentanyl) for colonoscopy and endoscopic retrograde cholangiopancreatography (ERCP). 10,23 Some studies have recommended propofol as a sedative in upper gastrointestinal endoscopy, but difficulties in estimating the correct dosage and the lack of a direct antagonist limit its use, particularly in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that greater central nervous sensitivity to intravenous anesthetics was affected in certain ways by liver dysfunction, such as by progressive cognitive dysfunction or slowing of brain activity (31). Hepatic dysfunction has already been demonstrated to enhance sensitivity to sedative agents (32). Therefore, it was suggested that the exact dose of propofol, administered by TCI for appropriate depth of anesthesia in patients with severe impaired liver function, requires further investigation.…”
Section: Discussionmentioning
confidence: 99%